2021
DOI: 10.3389/fgene.2021.697883
|View full text |Cite
|
Sign up to set email alerts
|

SLC4A11 and MFSD3 Gene Expression Changes in Deoxynivalenol Treated IPEC-J2 Cells

Abstract: Deoxynivalenol (DON) caused serious cytotoxicity for animal cells. However, genes involved in regulating DON toxicity and the underlying molecular mechanisms remain largely unknown. This study explored the role of SLC4A11 and MFSD3 in alleviating DON toxicity and analyzed the DNA methylation changes of these two genes. Viability and cell cycle analysis showed that DON exposure decreased the IPEC-J2 viability (P < 0.01), blocked the cell cycle in the G2/M phase (P < 0.01), and increased the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…DON has been especially known to be harmful to pigs; the reason for this is the high bioavailability, glucuronidation metabolism for excretion, lack of detoxification gut microorganisms, and long clearance time [38][39][40]. After the ingestion of DON, it may be rapidly absorbed and accumulate in the small intestinal tract, leading to antifeeding, vomiting, necrosis of the digestive tract, and a decrease in reproductive performance [41,42]. DON exposure causes diverse effects in various body systems, such as the gastrointestinal, neuroendocrine, and reproductive systems, intestinal toxicity, and results in growth impairment and immune dysfunction [36,43].…”
Section: Discussionmentioning
confidence: 99%
“…DON has been especially known to be harmful to pigs; the reason for this is the high bioavailability, glucuronidation metabolism for excretion, lack of detoxification gut microorganisms, and long clearance time [38][39][40]. After the ingestion of DON, it may be rapidly absorbed and accumulate in the small intestinal tract, leading to antifeeding, vomiting, necrosis of the digestive tract, and a decrease in reproductive performance [41,42]. DON exposure causes diverse effects in various body systems, such as the gastrointestinal, neuroendocrine, and reproductive systems, intestinal toxicity, and results in growth impairment and immune dysfunction [36,43].…”
Section: Discussionmentioning
confidence: 99%
“…There are several different groups including si- MLL1 -NC + DON, si- MLL1 + DON, si- TNFRSF1A -NC and si- TNFRSF1A . After treatments, the samples were performed as described previously [ 20 ]. Cell apoptosis and cell cycle were detected using flow cytometry (Beckman Coulter, Brea, CA, USA), and then analyzed by CytExpert 2.3 and FlowJo 7.6.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that DNA methylation plays a crucial role in maintaining cell function, regulating individual development and disease [2][3][4]. DNA methylation is considered to be a significant research hotspot in the current field of pig genetics and breeding, relevant studies mainly focus on tissue-specific expression [5,6], cell apoptosis [7], variety differences [8], growth and development [9][10][11], immune response [12,13]. However, DNA methylation has been rarely reported in expression regulation of pig resistance to pathogenic microorganism infection.…”
Section: Introductionmentioning
confidence: 99%